2020
DOI: 10.3389/fimmu.2020.590444
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence for the Association Between Epstein-Barr Virus Infection and Sjögren’s Syndrome

Abstract: Background: Exposure to Epstein-Barr virus (EBV) infection has been hypothesized to be an important risk factor for multiple rheumatic diseases, but the serological evidence so far for its role in Sjögren's syndrome (SjS) is not clearly established yet. This study aimed to assess the seroepidemiological associations of antibodies to EBV with SjS.Methods: A seroepidemiological study containing 119 patients with SjS and 65 healthy controls was first performed, in which the associations of SjS with four commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“… 18 A previous study found that SS patients had a significantly higher prevalence of IgG-anti-EA and IgG-anti-VCA antibodies (which are specific in population with acute EBV infections) than healthy controls, and patients with SS that had higher levels of IgG-anti-EA antibodies, which were linked to low levels of C3 and C4, in a case-control study. 19 Interferon (IFN) plays an important role in both the pathophysiology and clinical manifestations of SS. 20 Most SS patients express a “type I IFN signature” in immune cells, which drive the production of auto-antibodies and a range of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“… 18 A previous study found that SS patients had a significantly higher prevalence of IgG-anti-EA and IgG-anti-VCA antibodies (which are specific in population with acute EBV infections) than healthy controls, and patients with SS that had higher levels of IgG-anti-EA antibodies, which were linked to low levels of C3 and C4, in a case-control study. 19 Interferon (IFN) plays an important role in both the pathophysiology and clinical manifestations of SS. 20 Most SS patients express a “type I IFN signature” in immune cells, which drive the production of auto-antibodies and a range of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The autoreactive B cell hypothesis has also been proposed to drive systemic autoimmune diseases 21 . Elevated titres of one or more EBV antibodies have been identified in systemic lupus erythematosus, Sjogren's syndrome and rheumatoid arthritis 30–32 . As with MS, it is unclear whether differences in these antibody results implicate a role of EBV in autoimmune disease, or alternatively reflect differences in antibody production in patients with dysregulated immune systems.…”
Section: Mechanisms By Which Ebv Might Contribute To Ms Pathogenesismentioning
confidence: 99%
“… 21 Elevated titres of one or more EBV antibodies have been identified in systemic lupus erythematosus, Sjogren's syndrome and rheumatoid arthritis. 30 , 31 , 32 As with MS, it is unclear whether differences in these antibody results implicate a role of EBV in autoimmune disease, or alternatively reflect differences in antibody production in patients with dysregulated immune systems. Even though single‐nucleotide polymorphisms shared across MS and other autoimmune disorders can be identified in genome‐wide association studies (GWAS), clinical overlap is not a common phenomenon (although case reports do exist).…”
Section: Mechanisms By Which Ebv Might Contribute To Ms Pathogenesismentioning
confidence: 99%
“…SjS is a complex rheumatic disease characterized by the infiltration of immune cells into exocrine glands such as salivary glands, and effective targeted therapies for SjS are still lacking (1,2). Current studies suggest that some factors such as disease susceptibility genes, immune abnormalities, and viral infections are synergistically involved in its pathogenesis of SjS (3)(4)(5). Among those factors, abnormal immune factors such as B cell hyperactivity have been considered as key players in SjS pathogenesis and potential targets for SjS treatment (6,7).…”
Section: Introductionmentioning
confidence: 99%